Factors of city private transport decarbonization - Dekhnich, V.S.; Dronin, N.M. (Fundamental and Experimental Biology, 2022)
The article is devoted to assessing the contribution of greenhouse gas emissions from the transport sector of large cities and regional centers of the Republic of Kazakhstan. During the investigations we have calculated emissions from private automobiles in seventeen cities of Kazakhstan; declared the features of spatial differentiation of emissions by city districts; identified main factors of carbon intensity of motor transport in cities; determined quantitative indicators describing the significance of these factors, and provided an assessment of the significance of the considered factors. On the example of five representative cities (Nur-Sultan, Almaty, Shymkent, Ust-Kamenogorsk, Karaganda), the main spatial and geographical reasons for the decrease in the connectivity of the road network and the basic principles for reducing carbon intensity are identified. The studies are based on the data of the Committee on Statistics of the Republic of Kazakhstan, including statistical forms of the fuel and energy balance of the regions; demographic yearbooks; statistical collections containing information on the operation of transport; on the data of the open geoportals “Yandex Probki” and “Open Street Map”; on the results of GIS-calculations and on the methodological documents approved by IPCC.